DAYA TERIMA DAN ANALISIS PROTEIN SERTA ZAT BESI PADA CHEESE STIK DENGAN SUBSTITUSI TEPUNG KEDELAI - Lydia Fanny; Azha Mutia Rugaya; Hendrayati Hendrayati (Jurusan Gizi Poltekkes Kemenkes Makassar, 2021)
Background, Anemia is one of the nutritional problems experienced by many Indonesian adolescents, the prevalence of adolescents affected by anemia is 23.7%, one of the efforts and things that can be done to overcome the problem of anemia in adolescents is that which has been implemented by the government, one of which is the provision of blood-added tablets. TTD), and provide products that are loved by all audiences such as Cheese Sticks substituted with soy flour which is high in protein and iron.Purpose, of this study was to determine the acceptability and content of protein and iron content of Cheese Stick with soybean flour substitution.Design, The type of this research is laboratory research using Completely Randomized Design (CRD). The research sample used 25 panelists. Acceptance data was obtained from hedonic tests, protein and iron analysis data were obtained from the results of the chemistry SMK SMTI Makassar.Results, The results of the acceptability test showed that based on the results of statistical test s there was a significant difference in the color aspect with p<0.05 (0.000), there was no significant difference in the texture aspect with p<0.05 (0.140), there was a significant difference on the aroma aspect with p<0.05 (0.030). and there is a significant difference in the taste aspect with p<0.005 (0.000). The results of the analysis showed that the protein content of Cheese Sticks was the best, which was 8.6 g/100g and iron content was 2.064 g/100 g..conclusion, the most accepted formula based on aspects of color, texture, aroma and taste is F1.Suggestion, For further researchers, it is recommended to conduct further research by looking at or analyzing the content of other nutrients in cheese sticks with soy flour substitution.